Relevansi Akken Waghei (Angkat Keluarga) Mewujudkan Harmoni dalam Kebhinekaan di Kebandaran Mergo Sekampung Udik di Kabupaten Lampung Timur - Sainul Sainul; Fredy Gandhi Media (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2018)
Mores exists in the community, it happens repeatedly, snd it is supposed to be so. Adat that can lead to sanctions called customary law. Customary law occurs because of social contracts, binding on existing parties within the scope of mores. It treaties made to the public applicable as laws of law and protected by the state, the treaty made must be kept in the covenant of Islam as a debt. Misbehavior is the king's official statement of the recognition of the territorial autonomy of the kingdom that governed himself. Kebangaran Mergo Sekampung Udik is an autonomous region of the Banten government under the sultanate of Maulana Hasanudin. Maulana Hasanudin reigned over Pugung's unity in Lampung, after subduing Pugung's Keratuan through Marriage. In the indigenous communities of Lampung Mergo Sekampung Udik recognize custom Akken Waghei, customs that allow the adoption of family and carried out by adopting an Islamic pledge. Ankken waghei for local people is a solution to maintain good relationships, eradicate family problems, resolve disputes peacefully. Akken waghei can be done with any party, even between tribes. Akken waghei, important in ragka realize harmony in difference